POTENTIAL BAGGASE AND MOLASSES WASTE SUGAR FACTORY FOR MIXED SUBSTRATES WITH COW MANURE IN FERMENTATION PROCESS METHANOGENIC - Ludfia Windyasmara; Ambar Pertiwiningrum (Fakultas Peternakan Universitas Papua, 2018)
This study aims to analyze the potential of the sugar mill waste, namely baggase and molasses as a mixture of cow manure as a substrate in a methanogenic fermentation. This study uses 4 treatment that is P0 as controls (100% cow manure), later in other treatment using a mixture of cow manure comparison: baggase: molasses, P1 (50:20:30), P2 (50:30:20) and P3 ( 50: 40; 10). Parameters measured were nitrogen, carbon, ratio C / N and pH value. The analyze used in this research is statistic analysis. The results were obtained P3 which is a mixture of substrate (50:40:10) has an average value of the content of nitrogen, carbon, ratio C / N, and high pH value is compared to the other treatments. Ratio C / N at P3 of 24.47 closest Ratio C / N ideal for methanogenic fermentation which amounted to 25. The pH value of the treatment amounted to 7.05 billion P3 also meet the standards for process fermentation ranging from 6.6 to 7.6.